Freedmen's Bureau Act on July 16, 1866, §14 - (:unkn) unknown (My University, 1866)
Declared that full and equal benefit of all laws and proceedings concerning personal liberty, security, acquisition, enjoyment, and disposition of estate, including the right to bear arms, shall be secured and enjoyed by all citizens.Without respect to race, color, or previous status as a slave.
Keywords: GUARANTEED RIGHT